Environmental and genetic constraints on cuticular hydrocarbon composition and nestmate recognition in ants. (January 2020) - Villalta, Irene; Rami, Léa; Alvarez-Blanco, Paloma; Angulo, Elena; Cerdá, Xim; Boulay, Raphaël
Abstract : In insects, cuticular hydrocarbon (CHC) profiles are complex phenotypic traits with several functions: they provide protection against pathogens and water loss and convey information about insect identity. They are particularly important in ants as they are the basis for colony-specific signatures, which allow nestmate recognition and thus help colonies protect their resources from competitors. Several studies have shown that levels of n-alkanes are strongly influenced by the environment and that, alongside methyl-branched alkanes, n-alkanes are involved in various signalling tasks. Here, we analysed the CHCs of the ant Aphaenogaster iberica along an elevational gradient running from sea level to 2000 m. Across this gradient, we found a considerable difference in mean daily temperature of more than 10 °C between the populations on either end of the gradient as well as a marked degree of genetic structuring among populations. Moreover, genetic distance between populations increased with elevational distance but was independent of horizontal distance. Low-elevation populations had larger amounts of heavier compounds, including nonacosane (C29), and smaller amounts of lighter compounds, including hexacosane (C26) and heptacosane (C27). The level of aggression among non-nestmates increased with elevational distance, horizontal distance and CHC dissimilarity. However, mean within-population aggression (i.e. among colonies of the same population) did not differ across elevation. We also found that aggression was related to CHC levels: the correlation between the level of aggression and CHC dissimilarity remained significant even after we accounted for the correlation between genetic distance and aggression. We propose that climatic differences at different elevations may constrain CHC diversity and, consequently, the process of nestmate recognition. Highlights: Cuticular hydrocarbons (CHCs) help ants protect themselves and communicate. Levels of n -alkane are strongly influenced by the environment. Variation of CHCs with elevation has consequences for nestmate recognition. Global warming may impact ant behaviour through pleiotropic traits like CHCs.